One of the binding proteins for administered amyloid-β appears to be anti-Aβ IgG antibody in amyloid plaques - Takahashi, Reisuke H; Yokotsuka, Mayumi; Nakamura, Ayako; Nagao, Toshitaka; Gouras, Gunnar K ; 0000-0002-5500-6325; Uchihara, Toshiki (Journal of Alzheimer's disease : JAD, 2025)
BackgroundAmyloid-β peptides (Aβ) applied to Alzheimer's disease (AD) brain bind to amyloid plaques (APs) and this binding is saturable. Meanwhile, anti-immunoglobulin G (IgG) antibodies label APs. Considering the saturable binding of Aβ to APs and the localization of IgGs in APs, specific binding proteins (BPs) for the applied Aβ could be anti-Aβ IgG antibodies (anti-AβAbs) in APs.ObjectiveOur objective is to demonstrate whether anti-AβAbs are the BPs for administered Aβ in APs.MethodsTo identify the binding specificity, we established a tissue competition assay utilizing the competitiveness of ligand specificity to BPs. Biotinylated Aβ 42 (Bio42) was applied as ligand to AD brain sections. Second, Bio42 and IgG (anti-AβAbs) in APs were observed by double immunofluorescent labeling with ultrahigh-resolution imaging. Finally, to demonstrate the direct binding of Bio42 to anti-AβAbs we employed immunoprecipitation-western blotting.ResultsWith the tissue competition assay, binding of Bio42 to APs was competitively blocked by coincubation with competitive Aβ 42 (Pep42) in a dose-dependent manner but not with non-competitive Aβ 40 (Pep40). Colocalization of Bio42 and anti-AβAbs was clearly detected with ultrahigh-resolution imaging. Anti-AβAbs were immunoprecipitated by Bio42 and immunoblotted by anti-IgG antibodies.ConclusionsWe have provided evidence that the applied Aβ specifically binds to anti-AβAbs rather than aggregating with Aβ in APs. Our results support the scenario that anti-AβAbs surround and/or sequester Aβ from biological fluids to APs, thereby affecting the amount of Aβ in body fluids. It might be important to consider anti-AβAbs in APs for more effective diagnosis and therapy for AD.